Contemporary Computer Network Infrastructure Transformation: Performance Management, Internet of Things (IoT) Convergence, and Cybersecurity Resilience - Muhammad Zaky Adima Putra; Ima Firda Fradilla; Fauzan Masykur (PT Mekar Research and Publishing, 2026)
The development of information technology over the past decade has demanded a massive restructuring of computer network architecture. Infrastructure that previously focused solely on local area network (LAN) connectivity has now radically transformed into a hybrid ecosystem that integrates cloud computing, Software-Defined Networking (SDN) infrastructure, billions of 5G-enabled Internet of Things (IoT) devices, and demands a layered cybersecurity architecture powered by artificial intelligence (AI). This article aims to present a comprehensive literature review of three key pillars of modern computer networks: (1) performance optimization through automated bandwidth management and AI-driven QoS implementation; (2) network convergence and scalability to accommodate IoT devices in the agriculture, civil infrastructure, and logistics sectors; and (3) cybersecurity risk mitigation amidst an expanding attack surface. Using a systematic literature review, this study identifies that the implementation of intelligent traffic management not only reduces latency but also maintains stability (throughput). Furthermore, IoT integration requires 5G connectivity and lightweight communication protocols for high availability. This increased interconnectivity has serious implications for cyber resilience, urgently requiring the implementation of Zero Trust architecture, machine learning-based intrusion detection, and regular encryption system updates. This article provides a strong theoretical foundation for the development of future network infrastructure while highlighting the importance of preparing human resources through vocational education in information technology.